In vitro Propagation in Three Varieties of Gerbera (Gerbera jamesonii Bolus.) from Flower Bud and Flower Stalk Explants - Akter, Nazma; Hoque, MI; Sarker, RH (Plant Tissue Culture and Biotechnology, 2013)
Three types of tender leaves derived explants such as leaf tip, leaf with mid-rib and leaf blade segments as well as flower buds and flower stalks obtained from three selected varieties of gerbera (Gerbera jamesonii Bolus.) cultivated in Bangladesh were exploited for callus induction and in vitro regeneration of plantlets. Among the explants flower bud and flower stalk were suitable and superior for callus induction and subsequent regeneration of in vitro shoots when cultured on MS supplemented with 5.0 mg/l BAP and 1.0 mg/l NAA. However, highest number of multiple shoots were obtained when the flower bud derived callus was subcultured on MS supplemented with 2.0 mg/l BAP. Variety with red petal showed the best response in producing multiple shoots among the three varieties. Root induction at the base of the in vitro regenerated shoots was tried using full and half the strengths of MS containing different concentrations of IBA. Best root induction was observed on half the strength of MS supplemented with 0.2 mg/l IBA. Following adequate acclimatization the regenerated plantlets were successfully transferred to soil where they grew to maturity and produced flowers. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14203 Plant Tissue Cult. & Biotech. 22(2): 143-152, 2012 (December)